posted by Soly on .
I need help with the following problem:
Solve the equation:
(x/2x+2)= (-2x/4x+4) + (2x-3/x+1)
I am not sure whether I am interpreting your question correctly.
.5x + 2 = -.5x + 4 + 2x - 3/x + 1
First, get all the x terms on one side.
.5x + .5x - 2x + 3/x = 4 + 1 - 2
-x + 3/x = 3
Multiply both sides by x to get rid of x in the denominator.
-x^2 + 3 = 3x
-x^2 - 3x + 3 = 0
Multiply by -1.
x^2 + 3x - 3 = 0
Unfortunately, I cannot factor this to find possible answers. Are there any typos in your equation?
I hope this helps a little. Thanks for asking.
lol sorry i was suppose to give you the answer..i have never done this before...